PENGEMBANGAN KURIKULUM PENDIDIKAN BERBASIS NILAI CINTA DAN TEKNOLOGI - Ermiza Ermiza; Nurhayani Nurhayani; Syukra Laili; Sri Wahyuningsih (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
The development of digital technology has brought significant changes in the world of education, especially in curriculum development. However, this progress also poses challenges in the form of educational tendencies that are technocratic and have the potential to ignore human values. This research aims to examine the development of an educational curriculum based on the values of love and technology as an effort to integrate humanistic and digital dimensions in education. This research uses a qualitative approach with the library research method, with data sources in the form of books, reputable scientific journal articles, as well as relevant educational policy and curriculum documents. Data analysis is carried out through content analysis techniques with stages of data reduction, theme categorization, and conclusion drawn. The results of the study show that the value of love acts as a normative and ethical foundation in the curriculum that emphasizes empathy, care, and character formation of students, while technology functions as a pedagogical means to increase the effectiveness, flexibility, and relevance of learning. The integration of the values of love and technology in the curriculum allows for the creation of a holistic, meaningful, and sustainable educational process. This research is expected to make a theoretical contribution to the development of a humanistic and adaptive curriculum paradigm to technological developments.